The Influence of Training and Work Discipline on the Performance of PT Kereta Api Indonesia (Persero) Building Unit Employees Divre III Palembang LRT SUMSEL Maintenance Area - Triana Agustini; Jamilah Pramajaya; Bayu Singgalang (UNIVED Press, 2024)
The aim of this research is to determine the Influence of Training and Work Discipline on the Performance of PT Kereta Api Indonesia (Persero) Building Unit Employees Divre III Palembang LRT SUMSEL Maintenance Area. The method used is quantitative and qualitative analysis. Quantitative analysis is a research method based on the philosophy of positivism, used to research certain populations or samples, collecting data using research instruments, data analysis is quantitative or independent, with the aim of testing established hypotheses. Quantitative Analysis is used to see the results of the questionnaire using a literary scale. Based on the test results, the coefficient of determination (Adjusted R Square) was obtained at 0.773. This shows that the training and work discipline variables influence the performance variable by 77.3%. Meanwhile, the remaining 22.7% is explained by other variables not examined in this study.